Influencing policy and practice for young people in foster care: Learning from a model of collective participation. (June 2020) - Jackson, Rebecca; Brady, Bernadine; Forkan, Cormac; Tierney, Edel; Kennan, Danielle
Highlights: The rationale for ensuring participation in policy and service development for youth in care. A consideration of the requirements for, and barriers to, effective practice in this area. An introduction to a model of collective participation for young people in care. Consideration of participative rights in action through the frame of the Lundy (2007) model. Implications for practice. Abstract: A strong rationale for the collective participation of young people in care regarding decisions related to their care experience is evident in literature and statutory reports. However international research demonstrates challenges relating to participation in the childcare system. This includes context specific factors relating to issues in the field of child protection and welfare, along with more universal challenges such as access and diversity of representation, the imposition of adult formats and agendas and limits to the level of influence achieved. This paper reflects on the collective participation of young people in care in a rights-based initiative intended to facilitate input into service and policy development. This model, initiated by Tusla, Irelands Child and Family Agency, in partnership with EPIC an independent advocacy agency, provided an opportunity for young people in care to share direct experiences in order to identify and address challenges within the care system through meaningful collaborative processes. The perspectives of twenty-eight young participants were sought through five focus groups. In addition, twenty practitioners took part in semi-structured interviews. The design and analysis of these methods utilised a framework derived from Lundy's (2007) articulation of rights-based practice through the 'Voice Model'. Key lessons emerging suggest that a strong policy and legislative frame for practice underpinned by a model that articulates the practice requirements for effective participation is promising as evidenced by the outputs of the collective model. However, evidence of influence on policy and the service delivery experienced by children in care remains to be seen, as this process requires further time and organisational resources to embed and assess. Moreover, there is a need for the further development of communicative structures and feedback mechanisms if it is to be experienced as meaningful by all young people who engage with the model. Despite challenges in practice and the time required to achieve transformative influence, the personal benefits of direct participation in the fora for young people are arguably a worthy outcome of participatory practice.